Nadzwyczajne i zwyczajne źródła przeświadczeń i zachowań religijnych ludzi wierzących - Zimnica-Kuzioła, Emili (Poznańskie Studia Teologiczne, 2010)
The text deals with the issue of the religious beliefs of believers. The author refers to a range of scientific theories (sociological, psychological, theological and neurotheological) that explicate the phenomenon of religiosity. In parallel she presents the justification of faith given by ordinary believers who also point to supernatural sources of religiosity. For them their inner experience is more important than rational (philosophical) arguments for the existence of the Absolute.